2003
DOI: 10.1111/j.1651-2227.2003.tb02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial distress during pregnancy and the risk of infantile colic: a follow‐up study

Abstract: Aim: To examine the association between psychosocial exposures during pregnancy and the risk of infantile colic. Methods: The study included 378 infants and was conducted as a substudy of the Danish National Birth Cohort from 1997 to 1999, with prenatal data collected twice during pregnancy. A diary with a record for postpartum weeks 4–8 was used to quantify the amount of the infants' crying and fussing. Results: The cumulative incidence proportion of infantile colic was 8.2%. A threefold increased risk of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…We therefore conducted a retrospective cohort study nested within a completed randomized controlled trial (RCT) 14 to investigate longitudinal associations of inconsolable infant crying at 5 to 6 weeks of age with maternal depressive symptoms at 8 weeks postpartum, while controlling for preexisting depression, which may influence infant colic [15][16][17] and irritability. 18 We hypothesized that prolonged inconsolable infant crying, rather than the total daily duration of distress (ie, colic), would have a stronger longitudinal association with maternal depression symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore conducted a retrospective cohort study nested within a completed randomized controlled trial (RCT) 14 to investigate longitudinal associations of inconsolable infant crying at 5 to 6 weeks of age with maternal depressive symptoms at 8 weeks postpartum, while controlling for preexisting depression, which may influence infant colic [15][16][17] and irritability. 18 We hypothesized that prolonged inconsolable infant crying, rather than the total daily duration of distress (ie, colic), would have a stronger longitudinal association with maternal depression symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the subjective maternal assessments might have been affected by confounding psychosocial factors associated with infantile colic. 13,14 Several mothers of infants who had failed to respond to dietary treatment, as indicated by the cry charts, categorized their infants as "better" at the end of the study, which suggests that the assessments might also have been influenced by placebo and/or Hawthorne effects.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,11,12 Several psychosocial factors and maternal smoking have been shown to increase the risk of infantile colic. 13,14 The role of diet in infantile colic is controversial. 5 Among formula-fed infants with colic, use of extensively hydrolyzed casein-and whey-based preparations is associated with significant improvement in colic symptoms.…”
mentioning
confidence: 99%
“…Sondergaard et al (2003) found a threefold increase of having an infant with colic if the mother reported general stress during pregnancy, and twice as likely if they reported psychological stress; however, as the data were collected retrospectively, it has been suggested that the mothers' reports of stress might be heightened if dealing with a crying baby, and so no causal relation can be certain (St James-Roberts & Conroy, 2005). More recently, Wurmser et al (2006), carried out a prospective longitudinal study and found that those mothers who reported higher levels of stressful life events during pregnancy had infants who cried more within the first 6 months of life than did mothers with lower stress scores.…”
Section: Definitionmentioning
confidence: 97%